Constrictive pericarditis in a young patient with very thick pericardium initially diagnosed as cirrhosis. (December 2013) - Durmus, Erdal; Sunbul, Murat; Kivrak, Tarik; Sari, Ibrahim; Mutlu, Bulent
Constrictive pericarditis (CP) is a disease of pericardium that restricts filling of the heart. Patients with CP generally present to hospitals with exercise-induced dyspnea, pretibial edema and abdominal ascites, and it is sometimes mistakenly diagnosed as liver or renal disease. Pericardial thickening, which is defined as more than 4 mm in diameter, is observed in nearly 80% of patients. In the present paper, we describe a case of CP with a pericardial thickness of 12 mm that was initially diagnosed as cirrhosis.